The Implications of Muhammad Arkoun’s Hermeneutical Thought for Hadith Studies: An Examination of the Problematics in Hadiths on Hand-Cutting Punishment and Marriage Guardianship - Khoir, Moh Misbakhul; Idri (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Hermeneutics as a new methodology plays a vital role in complementing and providing methodological solutions to the legacy of conventional Islamic science, which is considered unable to solve contemporary problems. This paper aims to explain the use of Muhammad Arkoun’s hermeneutics in Hadith studies, especially regarding the issue of the punishment of hand cutting and marriage guardianship in the contemporary context. In reading the two Hadiths, Arkoun’s ideas effectively present a new perspective more relevant to the times. In this way, religion will always be appropriate to human needs throughout time and space. However, the presence of Arkoun’s hermeneutics also leads to the emergence of diverse new interpretations, so that the potential for flooding religious information will be increasingly open. This condition certainly impacts the community; they will have difficulty finding the spiritual information they expect. Secondly, hermeneutics as an effect of Western humanist thought has the potential to change the order of life from God-centred (theocentrism) to human-centred (anthropocentrism) with its intellect. This universe is God’s creation. All of his creations should be subject to the provisions given by God, not the other way round. This triggers a long debate that never ends.